Manufacturing competitiveness in East Asia : an empirical assessment - Chan, Sarah Siaw Fume (2015)
Much of East Asia's growth and development over the past few decades has been built on its competitiveness in manufacturing. This research seeks to examine the factors driving the competitiveness of seven economies - China, South Korea and the ASEAN-5 countries of Malaysia, Thailand, Indonesia, Singapore and the Philippines - in the manufacturing sectors from 2000 to 2010. Since the competitiveness of manufacturing can be broadly defined as the ability to produce manufactured products that can compete on international markets, this study uses export trade data of the East Asian economies as a proxy for their manufacturing competitiveness. Employing a panel and pooled data estimation technique, the study finds that unit labour costs, infrastructure, real exchange rates and global demand are crucial determinants behind manufacturing competitiveness. The empirical results suggest that policy measures to reduce trade barriers, lower unit labour costs by improving labour productivity through education and skills training as well as developing infrastructure are vital in boosting manufacturing competitiveness. Liberalising the services sectors is also essential as manufacturing requires good access to high-quality financial services, for instance. Faced with a more challenging internal and external environment such as rising costs emanating from rapid demographic changes or the threat of potential protectionism from the developed nations, the East Asian countries may also need to further implement certain structural reform measures like improving the quality of institutions or strengthening governance so as enhance their attractiveness as an investment destination and further fostering greater intra-regional trade.